Implications of regulatory T cells in anti-cancer immunity: from pathogenesis to therapeutics. Issue 8 (August 2022) - Dwivedi, Mitesh; Tiwari, Sanjay; Kemp, E. Helen; Begum, Rasheedunnisa
Abstract: Regulatory T cells (Tregs) play an essential role in maintaining immune tolerance and suppressing inflammation. However, Tregs present major hurdle in eliciting potent anti-cancer immune responses. Therefore, curbing the activity of Tregs represents a novel and efficient way towards successful immunotherapy of cancer. Moreover, there is an emerging interest in harnessing Treg-based strategies for augmenting anti-cancer immunity in different types of the disease. This review summarises the crucial mechanisms of Tregs' mediated suppression of anti-cancer immunity and strategies to suppress or to alter such Tregs to improve the immune response against tumors. Highlighting important clinical studies, the review also describes current Treg-based therapeutic interventions in cancer, and discusses Treg-suppression by molecular targeting, which may emerge as an effective cancer immunotherapy and as an alternative to detrimental chemotherapeutic agents. Highlights: Tregs are crucial in maintaining immune tolerance and suppressing inflammation. Tregs present a major obstacle to eliciting potent anti-tumor immune responses. The review summarizes current Treg-based therapeutic interventions in cancer. Treg can be an effective cancer immunotherapy target. Abstract : Anti-cancer immunity; Cancer, CD8 + T cells; CD4 + T cells; Regulatory T cells; Tumor-infiltrating lymphocytes.